(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The aim of this study is to determine the weldability of different materials - AISI 316L stainless steel and carbidic austempered ductile iron (CADI) by electron beam welding (EBW). Welding is performed with different beam current (Ib) of 10 mA and 20 mA, welding speed (V) of 400 mm/min and 1000 mm/min with an offset relative to the stainless steel of 0.2 mm at a constant frequency deviation (Freq). Vickers microhardness is measured in the fusion zone (FZ) and in the heat affected zones (HAZ). The most suitable welding mode is determined in terms of higher microhardness in the FZ with the presence of defects in the weld seam.